For euthanasia. Minimum notes on the right to decide life and health (Nóema, 2013)
After recalling that according to recent sentences of the European Court of human rights «an individual’s right to decide by what means and at what point his or her life will end, provided he or she is capable of freely reaching a decision on this question and acting in consequence, is one of the aspects of the right to respect for private life within the meaning of Article 8 of the Convention», and illustrating the Christian world‘s dissenting opinions on euthanasia in contrast to the Magisterium of the Catholic Church, the author examines the bills  presented to the Italian parliament to regulate the matter.
Keywords: euthanasia; right to die with dignity; European Court of human rights